FACTOR INFLUENCING MIGRATION AND JOB SATISFACTION AMONGST PAKISTANI NURSES: A STUDY OF PUSHING AND PULLING FACTORS IN MULTAN INSTITUTE OF CARDIOLOGY AND NISHTAR HOSPITAL MULTAN - NAZ , S; MAJEED , S; BUKHARI , J; BASHEER , N (Biological and Clinical Sciences Research Journal, 2024)
The nursing workforce plays a critical role in healthcare delivery; however, job dissatisfaction and migration intentions among nurses pose significant challenges, particularly in low- and middle-income countries like Pakistan. Factors such as low wages, poor working conditions, and lack of professional development contribute to dissatisfaction and workforce shortages. Objective: To explore factors influencing job satisfaction and migration intentions among nurses at Multan Institute of Cardiology (MIC) and Nishtar Hospital, Multan. Methods: A descriptive cross-sectional survey was conducted at MIC and Nishtar Hospital, involving 250 nurses using stratified random sampling. Data were collected using a validated structured questionnaire addressing demographic characteristics, job satisfaction, and migration intentions. Responses were analyzed using SPSS version 26, with descriptive and inferential statistics. A p-value ≤0.05 was considered statistically significant. Results: The study revealed that 50% of nurses reported dissatisfaction with their jobs, primarily due to low wages (60%), poor working conditions (65%), and excessive workloads (70%). Migration intentions were significantly driven by higher salaries (75%) and better working conditions (70%) in destination countries. Professional development opportunities were identified as a major pull factor by 65% of nurses. Adverse events such as burnout and dissatisfaction were more prevalent among nurses with high workloads and inadequate workplace support. The results align with global studies emphasizing economic and professional growth as key motivators for migration. Conclusion: Low wages, poor working conditions, and lack of professional development are critical factors contributing to job dissatisfaction and migration intentions among nurses in Pakistan. Addressing these challenges through improved salaries, better working conditions, and enhanced professional development opportunities could improve nurse retention and reduce migration.